Temptation in the Archives - Jardine, Lisa (UCL Press, 2015)
Temptation in the Archives is a collection of essays by Lisa Jardine, that takes readers on a journey through the Dutch Golden Age. Through the study of such key figures as Sir Constantjin Huygens, a Dutch polymath and diplomat, we begin to see the Anglo-Dutch cultural connections that formed during this period against the backdrop of unfolding political events in England. Temptation in the Archives paints a picture of a unique relationship between the Netherlands and England in the 17th century forged through a shared experience - and reveals the lessons we can learn from it today.